Expressed Protein Selenoester Ligation. (9th March 2022) - Kulkarni, Sameer S.; Watson, Emma E.; Maxwell, Joshua W. C.; Niederacher, Gerhard; Johansen‐Leete, Jason; Huhmann, Susanne; Mukherjee, Somnath; Norman, Alexander R.; Kriegesmann, Julia; Becker, Christian F. W.; Payne, Richard J.
Abstract: Herein, we describe the development and application of a novel expressed protein selenoester ligation (EPSL) methodology for the one‐pot semi‐synthesis of modified proteins. EPSL harnesses the rapid kinetics of ligation reactions between modified synthetic selenopeptides and protein aryl selenoesters (generated from expressed intein fusion precursors) followed by in situ chemoselective deselenization to afford target proteins at concentrations that preclude the use of traditional ligation methods. The utility of the EPSL technology is showcased through the efficient semi‐synthesis of ubiquitinated polypeptides, lipidated analogues of the membrane‐associated GTPase YPT6, and site‐specifically phosphorylated variants of the oligomeric chaperone protein Hsp27 at high dilution. Abstract : An expressed protein selenoester ligation (EPSL) methodology that enables the efficient semi‐synthesis of site‐specifically modified proteins at high dilution is described. EPSL involves the one‐pot conversion of protein acyl hydrazides (derived from recombinant intein fusion precursors) to protein aryl selenoesters, followed by ligation with synthetic modified selenopeptides and chemoselective deselenization.